Developing attitude, love and value of art Education at the Secondary Stage - Singh, Huidrom Rakesh (International Journal of English Literature and Social Sciences (IJELS), 2019)
The aim of this paper is to show about the development of feelings, respect, discipline, honest are the essential requirement of all round personality development for learner through art education at secondary stage.